Effect of Azolla microphylla Incorporated Rations on Feed Intake and Nutrient Utilization of Punganur Bulls - Ega, Narendhar Reddy; Busineni, Devasena; Swarna, Venkateswarlu; Gollamoori, Gangaraju (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The present study was carried out to evaluate the effect of incorporation of fresh Azolla microphylla as replacement (0, 10, 20 and 30%) of crude protein content of concentrate mixture on feed intake, nutrient utilization and cost economics of Punganur bulls. In a 4 x 4 Latin square design, four mature Punganur bulls were fed with four different treatments, i.e., T1 ration (control) comprised of super napier (Cenchrus purpureus) ad libitum and concentrate mixture with 18% crude protein provided @ 0.5% of the body weight, while other groups T2, T3 and T4 were fed with ad libitum super napier along with the fresh Azolla microphylla to replace 10, 20 and 30% crude protein in concentrate mixture, respectively. A significant (p<0.01) improvement was observed in the digestibility (%) of dry matter, organic matter, crude protein, ether extract, crude fibre, acid detergent fibre, hemicellulose and nitrogen free extract (p<0.05) and was in the order of T4 >T3 > T2 > T1, while digestibility (%) of neutral detergent fibre and cellulose did not differ among the treatments. The DCP intake (kg/d) was highest (p<0.01) in T4 followed by T3, T2 and was lowest in T1. The DM and TDN intake (kg/d) during the experimental period did not differ significantly. It can be concluded that Azolla microphylla can replace up to 30% of the total protein in the concentrate mixture of mature Punganur bulls economically without any adverse effects.